On the atomic masses (weights?) Of the elements - Kaptay G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Atomic masses (weights?) is an essential information for mining and metallurgy. The paper discusses four subjects around this problem. First, the classification of all the elements is suggested into 4 classes, based on their isotope features, determining the accuracy of their known atomic masses. As part of that, the class of elements is discussed with uncertain atomic weights in accordance with the 2009 IUPAC recommendations. A better (easier to use) format of atomic weights is presented for this class of elements. Third, it is found not informative to leave empty spaces instead of approximate atomic weights for elements with unstable isotopes. Fourth, the term atomic weight vs the term atomic mass is discussed shortly, in agreement with the SI system of units and in contrary to the questionable IUPAC convection.